MUTU PELAYANAN KEPERAWATAN RUMAH SAKIT PURI HUSADA TEMBILAHAN - Five Indah Lestari; M.Kamali Zaman; Zulkarnaini Zulkarnaini (JOMIS (Journal of Midwifery Science), 2022)
The demand for nursing services is an important concern because nursing care occupies the top position in hospital services, giving rise to a response to the quality of nursing services in hospitals. The responses that emerged included the concept of nursing management and concrete steps in its implementation in a conducive manner. This study aims to analyze the quality of nursing services performed by nurses at Puri Husada Tembilahan Hospital. This research was conducted using a qualitative method with a femomenological design. The results of the study illustrate that the problems identified in the field of nursing consist of problems with the background of nurses' education, employment status, distribution of nurses and the quality of nursing services. The results of the analytical study carried out resulted in confirmation that the problems in the nursing field identified had influenced nurses in carrying out their main duties and functions. Nurses who cannot perform their main duties and functions properly will reduce the quality of nursing services in hospitals. It is recommended for hospital management to conduct a study of the quality of nursing services along with the nurse's background, the status of the nurse's workforce and the distribution of the nurse's workload.